A research on purchasing behavior of UiTM Sabah student on ball pen / Wilbur M Suinggi - Suinggi, Wilbur M (2008)
Based on the analysis of the survey, it was found that the findings and results of the survey are concurrent with literature and there some problem encountered and some suggestions to solve. Overall of this research, from the finding and analysis, researcher made the conclusion that most of the UiTM Sabah male students prefer 'Ordinary pens' and Stabilo brand which is the most popular brand. The male students mostly purchase their bags twice a year with blue colors as the color favorite. They also like to spend RM1 to RM4.99 to buy a pen.